Extra-parliamentary behaviour in Northern Ireland: MLAs and constituency service. Issue 4 (2nd October 2017) - Haughey, Sean
ABSTRACT: Little is known about the attitudes and behaviour of Northern Ireland's subnational legislators (Members of the Legislative Assembly, or MLAs) beyond their activities at Parliament Buildings, Stormont. This article provides the first analysis of MLAs' extra-parliamentary behaviour through a mixed-methods study of their constituency service. The study finds that MLAs attach considerable importance to constituency service, devoting more time to its provision than to parliamentary duties. Noticeable variation exists between and within parties in terms of constituency service effort, although unionist MLAs tend to have a stronger constituency focus than non-unionist MLAs. Variation in constituency service effort at the individual level has more to do with MLAs' role orientations than electoral incentives. In terms of their home style, MLAs exhibit local behaviour that is more characteristic of their contemporaries in the Republic of Ireland than their counterparts in the rest of the United Kingdom.